2020
DOI: 10.1002/jdd.12443
|View full text |Cite
|
Sign up to set email alerts
|

Student performance comparisons for a critical thinking skill set (technology decision‐making) for classroom and remote (Zoom) facilitation

Abstract: A comparison of student learning in a critical thinking exercise for technology decision‐making occurred with the onset of coronavirus and the switch from face‐to‐face to distance with Zoom. Literature on explicit critical thinking skill sets is scant in any format, including distance learning. While face‐to‐face and Zoom have similarities, seizing this opportunity for comparison can set the stage to determine soundness of distance learning in critical thinking on a preliminary basis. The learning outcome, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 9 publications
0
23
0
1
Order By: Relevance
“…Nine articles were categorized in this domain, with each study assessing students virtually. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Three of the studies were related to objective structured clinical examination (OSCE), a case‐based summative examination used for clinical assessment. 12 , 17 , 18 The remaining six articles focused on general online assessment, excluding the OSCE.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine articles were categorized in this domain, with each study assessing students virtually. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 Three of the studies were related to objective structured clinical examination (OSCE), a case‐based summative examination used for clinical assessment. 12 , 17 , 18 The remaining six articles focused on general online assessment, excluding the OSCE.…”
Section: Resultsmentioning
confidence: 99%
“… 12 , 17 , 18 The remaining six articles focused on general online assessment, excluding the OSCE. 13 , 14 , 15 , 16 , 19 , 20 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Zoom became a standard as a teleconferencing platform in teaching organizations more particularly during corona virus crisis, a few of private universities in the North of Iraq has adapted this platform as an alternative to face-to-face teaching (Holloway, Johnsen, & Syrbu, 2020). Hence, Major et al (2020) revealed that Zoom has an impact on learning experience positively, because of direct communication among students and lecturers which is mostly like face-to-face teaching.…”
Section: Online Educationmentioning
confidence: 99%